Overview of current practices on porous asphalt on highway application / Muhammad Mohktar Samat and Norizah Omar - Samat, Muhammad Mohktar; Omar, Norizah (Universiti Teknologi MARA Cawangan Pahang, 2008)
This paper presents an overview of current practice on porous asphalt on highway application. The main reason for considering the application of this particular type of road surfacing is the drainage characteristics of the surface layer. The drainage is made possible by the large percentage of voids up to 20% and that are interconnected, allowing water and air to flow towards the road shoulder. The use of porous asphalt offers a number of advantages such as reducing aquaplaning potential, improving skid resistance at high speed, reducing glare particularly on wet roads and an overall improvement in traffic safety. On the other hand, the disadvantages of porous asphalt compared to traditional road surfacings include short design life, high cost in terms of construction, maintenance and repair. However, porous asphalt has been applied in increasing quantities in European countries such as the Netherlands, France, Italy and Germany